Pterosaur Tracks from the Upper Cretaceous Anacleto Formation (Neuquén Basin), Northern Patagonia, Argentina: Insights into Campanian Pterosaur Diversity in Gondwana - Ignacio Díaz-Martínez; Arturo M. Heredia; Santiago N. González; Nerina Canale; Silvina de Valais; Carlos A. Cónsole-Gonella; Romina M. Montes; Martina Caratelli; Sofía Urzagasti-Torres; Geraldine Fischer; Agustina Lecuona; Pablo Paniceres; et al. (Diversity, 2022)
The Campanian Anacleto Formation holds an abundant and diverse ichnofossil and body-fossil vertebrate record. Despite the striking diversity of this record, pterosaur fossils had never been described from the unit. Here, we report four pterosaur manus tracks from fluvial red beds cropping out in the Área Natural Protegida Municipal Paso Córdoba (Río Negro Province, northern Patagonia, Argentina). Tracks are longer than wide, tridactyl with digit impressions of different lengths (I < II < III), anteriorly directed and laterally asymmetrical. Being on loose slabs and lacking direct examination of pes morphology, the material is classified as undetermined pterosaur tracks. The new find represents the first occurrence of pterosaurs from the lower–middle Campanian of Argentina and one of the few evidences from South America for this time interval. In addition, it is one of the few ichnological pterosaur records from Gondwana, thus shedding light on the palaeobiogeography of this clade during the latest Cretaceous. Pterosaur tracks from the Anacleto Formation allow us to integrate the body-fossil record from the unit and to add a new component, along with birds, to the flying archosaur fauna coexisting with non-avian dinosaurs, notosuchians, chelonians, squamates and mammals in the Campanian of northern Patagonia.